Fruit and vegetable consumption by South African children, aged 12 to 108 months : a secondary analysis of the National Food Consumption Survey data - Naude, Celeste (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Human Nutrition))--Stellenbosch University, 2007.